2007
DOI: 10.1016/j.biomaterials.2006.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Auto-catalytic ceria nanoparticles offer neuroprotection to adult rat spinal cord neurons

Abstract: This paper describes the evaluation of the auto-catalytic anti-oxidant behavior and biocompatibility of Cerium oxide nanoparticles for applications in spinal cord repair and other diseases of the CNS. The application of a single dose of nano-Ceria at a nano-molar concentration is biocompatible, regenerative and provides a significant neuroprotective effect on adult rat spinal cord neurons.Retention of neuronal function is demonstrated from electrophysiological recordings and the possibility of its application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
512
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 694 publications
(523 citation statements)
references
References 33 publications
8
512
1
2
Order By: Relevance
“…35 In addition, nanoceria improved the function and survival of rat spinal cord neurons exposed to H 2 O 2 . 47 Furthermore, nanoceria protected HT22 cells, a hippocampal neuronal cell line, from glutamate-induced cell death. 48 CeO 2 nanoparticles also seem to be protective in the eye.…”
Section: Discussionmentioning
confidence: 99%
“…35 In addition, nanoceria improved the function and survival of rat spinal cord neurons exposed to H 2 O 2 . 47 Furthermore, nanoceria protected HT22 cells, a hippocampal neuronal cell line, from glutamate-induced cell death. 48 CeO 2 nanoparticles also seem to be protective in the eye.…”
Section: Discussionmentioning
confidence: 99%
“…There are two methods by which living systems remove hydroxyl radicals: blocking hydroxyl radical initiation by antioxidant enzymes (SOD, glutathione peroxidase and catalase) or breaking the hydroxyl radical chain reaction using nonenzymatic antioxidants. 49 Hickman and co-workers 53 found that ultrafine CeONP (2-5 nm) with mixed valence states had a significant neuroprotective effect on H 2 O 2 -treated adult spinal cord model systems designed to prevent oxidative injury. As H 2 O 2 provides a source of hydroxyl radicals, which have a major role in oxidative injury, Hickman and coworkers 53 proposed that the protective effect of CeONP on the spinal cord involved its free-radical scavenging effect.…”
Section: Hydroxyl Radical Scavengingmentioning
confidence: 99%
“…In in vivo rat studies, the nanoparticles (0.1-1 mM) were injected into the vitreous humor of both eyes and shown to prevent loss of vision due to the light-induced degeneration of photoreceptor cells (60). Cerium oxide nanoparticle (at nanomolar levels) proved beneficial in an in vitro cell model of adult rat spinal cord neuroprotection (78). These nanoparticles (3-5 nm) can also protect normal tissue against radiation-induced damage; CeO 2 nanoparticles prevented the onset of radiation-induced pneumonitis when delivered (IP or IV) to athymic nude mice exposed to high doses of radiation in a study using amifostine as a positive control (63).…”
Section: Other Compoundsmentioning
confidence: 99%